Early child care and maternal employment: Empirical evidence from Germany - Franziska Zimmert (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2019)
This paper examines the effect of an expansion of subsidized early child care on maternal labor market outcomes. It contributes to the literature by analyzing, apart from the employment rate and agreed working hours, preferred working hours. Using the legal claim for subsidized child care introduced in Germany in August 2013 for children aged one to three years, I apply a semi-parametric difference-in-differences estimator to examine maternal labor market outcomes. Findings based on survey data from the German Micro Census show a positive effect on the employment rate, as well as on agreed and preferred working hours in districts where the child care coverage rate increases intensely in contrast to districts with a lower expansion of subsidized child care. As agreed and preferred working hours adjust in line with each other, expansion of early child care can tap labour market potentials beyond those of currently underemployed mothers. – – Das vorliegende Papier untersucht nicht nur den Effekt der Verfügbarkeit von öffentlicher Kinderbetreuung auf die mütterliche Erwerbsquote und den vereinbarten Stundenumfang, sondern auch auf die gewünschte Stundenzahl. Dabei wird der im August 2013 eingeführte Rechtsanspruch auf einen Betreuungsplatz für Kinder ab dem ersten Lebensjahr genutzt, um einen semi-parametrischen Differenzen-von-Differenzen-Ansatz anzuwenden. Die Ergebnisse auf Basis des Mikrozensus deuten auf einen positiven Effekt auf die Erwerbsbeteiligung und auf vereinbarte und gewünschte Arbeitsstunden in Landkreisen, in denen die Kinderbetreuungsquote intensiv anstieg, im Vergleich zu Landkreisen mit einem geringeren Anstieg dieser Quote, hin. Da sich gewünschte und vereinbarte Arbeitszeit gleichermaßen erhöhen, hat die Ausweitung von frühkindlicher Betreuung Arbeitsmarktpotentiale über die Gruppe der unterbeschäftigen Mütter hinaus.
Keywords: J21; J22; 330; maternal labor supply; working hour preferences; subsidized child care; early child care; semi-parametric difference-in-differences